2011
DOI: 10.1590/s0004-282x2011000300021
|View full text |Cite
|
Sign up to set email alerts
|

Semi-quantitative analysis of the effects of cyclosporine on remyelination following gliotoxic injection in the brainstem

Abstract: The use of cyclosporine (CsA) has shown to induce an increase in the density of oligodendrocytes near remyelinating areas following the injection of ethidium bromide (EB), a demyelinating agent, in the rat brainstem. This study was designed in order to evaluate if CsA has the capacity of increasing remyelination. In this context, a comparison between the final balance of myelin repair in CsA treated and non-treated rats was assessed using a semi-quantitative method developed for documenting the extent and natu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
6
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(7 citation statements)
references
References 21 publications
1
6
0
Order By: Relevance
“…In our study, there was no apparent difference regarding astrocyte, lymphocyte, or macrophage presence in the EB‐induced lesions between both groups (treated or not with PPF). Lesions were similar to those found in this toxic model (Blakemore, ; Bondan et al, ; Graça and Blakemore, ; Pereira et al, ; Yajima and Suzuki, ); however rats treated with PPF presented lesions that resembled those observed with CsA treatment (Bondan et al, ; Bondan and Martins, ), with a higher density of oligodendrocytes over the edges of the lesions and increased remyelination. The precise mechanisms by which these beneficial PPF effects occur remain obscure.…”
Section: Discussionsupporting
confidence: 76%
See 3 more Smart Citations
“…In our study, there was no apparent difference regarding astrocyte, lymphocyte, or macrophage presence in the EB‐induced lesions between both groups (treated or not with PPF). Lesions were similar to those found in this toxic model (Blakemore, ; Bondan et al, ; Graça and Blakemore, ; Pereira et al, ; Yajima and Suzuki, ); however rats treated with PPF presented lesions that resembled those observed with CsA treatment (Bondan et al, ; Bondan and Martins, ), with a higher density of oligodendrocytes over the edges of the lesions and increased remyelination. The precise mechanisms by which these beneficial PPF effects occur remain obscure.…”
Section: Discussionsupporting
confidence: 76%
“…As previously observed, the inhibition of IL‐2 secretion induced by cyclosporine (CsA) stimulated oligodendrocyte remyelination in rats (Bondan et al, ), even in diabetic rats (Bondan and Martins, ). On the other hand, Saneto et al () noticed that IL‐2 presence was capable of inhibiting the proliferation of oligodendrocyte progenitor cells (OPCs) in vitro even though stimulating their maturation in adult oligodendrocytes.…”
Section: Discussionmentioning
confidence: 65%
See 2 more Smart Citations
“…Using a semi‐quantitative method developed by Gilson and Blakemore () for documenting the extent and nature of remyelination in gliotoxic lesions, it was clearly demonstrated that in vivo administration of CsA after EB‐demyelinating process stimulated oligodendrocyte remyelination, although the mechanisms by which that positive effect occurred remained unclear (Bondan et al, ). It was suggested that CsA could produce a direct or indirect effect on persisting niches of OPCs in the mature CNS environment, thus affecting the final balance between proliferative/antiproliferative factors related to oligodendroglial populations in the lesion site, maybe facilitating the former and resulting in greater numbers of oligodendrocytes.…”
Section: Introductionmentioning
confidence: 99%